The influence of role conflict, job satisfaction, and organizational commitment to turnover intention on female teacher - Reny Martha Linda; Ani Muttaqiyathun (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The role of women's transition as laborers actively participates in economic activities (earning a living) in various activities following the skills and education they have as well as available job opportunities. No exception is a kindergarten teacher. This study aims to determine the effect of role conflict, job satisfaction, and organizational commitment on the turnover intention of working women, in this case, the kindergarten teacher ABA Full Day in Yogyakarta. The sampling technique uses saturated sampling. The sample was 56 people—data collection using a questionnaire survey method. Test the instrument using a validity test and reliability test. Data analysis using regression test. The result of the research concludes that role conflict and organizational commitment have a significant effect on turnover intention. In contrast, job satisfaction has no significant effect on turnover intention. However, role conflict, job satisfaction, and organizational commitment significantly affect turnover intention. These findings provide a thought-provoking insight into the difficulties encountered by female teachers, underscoring the vital need to tackle these factors in order to cultivate a supportive and nurturing educational atmosphere.